How Reproducible are Surface Areas Calculated from the BET Equation? (Adv. Mater. 27/2022). Issue 27 (7th July 2022) - Osterrieth, Johannes W. M.; Rampersad, James; Madden, David; Rampal, Nakul; Skoric, Luka; Connolly, Bethany; Allendorf, Mark D.; Stavila, Vitalie; Snider, Jonathan L.; Ameloot, Rob; Marreiros, João; Ania, Conchi; et al.
Abstract : Nanoporous Materials In article number 2201502, David Fairen‐Jimenez and co‐workers conduct a round‐robin exercise by providing 18 already‐measured adsorption isotherms to sixty‐one labs and show that the reproducibility of the Brunauer–Emmett–Teller (BET) area determination in micro‐ and mesoporous materials remains a largely ignored issue. To solve this, a new computational approach—called BETSI—that expands on the Rouquerol criteria and makes an unambiguous BET area assignment possible is developed.